Trends in Acupuncture Therapy for Microcirculation and Hemorheology from 1998 to 2023: A Bibliometric and Visualized Study - Wang Q; Zhang Q; Lu F; Hu H; Zhu M (Journal of Pain Research, 2024)
Qi Wang,1,2 Quanai Zhang,1 Fengyan Lu,1 Hantong Hu,1 Muru Zhu2 1Department of Acupuncture and Moxibustion, The Third Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China; 2Third Clinical Medical College, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Quanai Zhang, Department of Acupuncture and Moxibustion, The Third Affiliated Hospital of Zhejiang Chinese Medical University, NO. 219 Moganshan Road, Hangzhou, Zhengjiang, 310005, People’s Republic of China, Tel +86 0571 88075439, Email 20071029@zcmu.edu.cnBackground: The aim of this study is to explore and illustrate the focal points concerning acupuncture’s impact on microcirculation and hemorheology over the past 26 years, and to identify future directions in this field.Methods: Data in this area were gathered from the Web of Science Core Collection database. Employing CiteSpace, VOSviewer, Scimago Graphica, and Microsoft Excel software, we analyzed authors, institutions, and countries to evaluate scientific collaboration. Moreover, we carried out an analysis of keyword clustering, references, and burst detection to examine the prominent research areas and emerging trends in this domain.Results: The study analyzed 706 documents, 471 institutions, 632 journals, 40 countries, 581 keywords, and 3289 authors related to acupuncture for microcirculation and hemorheology. Data revealed a consistent increase in research output over 26 years. China, with the most publications and citations, significantly contributed to the field, often collaborating with the United States. Elisabet Stener-Victorin and the China Academy of Chinese Medical Sciences were the most productive author and institution, respectively. The journal Evidence-based Complementary and Alternative Medicine held the most influence. Common keywords included “vasoactive substances”, “neurotransmitters”, “signaling pathways”, and “oxidative stress”, among others. Research topics focused on female infertility, ischemic stroke, and pain syndromes, with treatment approaches such as electroacupuncture, manual acupuncture, auricular acupuncture, and cupping therapy.Conclusion: Women’s infertility, ischemic stroke, and pain syndromes have emerged as hotspots in research. Future directions may include comparative studies of traditional and modern acupuncture techniques to evaluate their respective therapeutic effects. There is potential for in-depth research in these areas and the discovery of new intervention strategies as well as mechanisms.Keywords: acupuncture, microcirculation, hemorheology, bibliometric analysis, visual analysis, pain